A cyclic adenosine monophosphate response element-binding protein inhibitor enhances the antibacterial activity of polymyxin B by inhibiting the ATP hydrolyzation activity of CrrB - Huang, Wei; Zhang, Jinyong; He, Yuzhang; Hu, Chunxia; Cheng, Shumin; Zeng, Huan; Zheng, Manling; Yu, Huijuan; Liu, Xue; Zou, Quanming; Cui, Ruiqin (Frontiers in Pharmacology, 2022)
The emergence of polymyxin B (PB) resistant Gram-negative bacteria pose an important clinical and public health threat. Antibiotic adjuvants development is a complementary strategy that fill the gap of new antibiotic. Here we described the discovery of the enhancement capacity of compound 666-15, previously identified as an inhibitor of cyclic adenosine monophosphate response element-binding protein (CREB), on the activity of PB against Klebsiella pneumoniae in vitro and in vivo. Mechanistic studies showed that this compound reduced the transcription and translation levels of genes related to lipid A modification in the presence of PB. We also identified that 666-15 reduce the ATP hydrolyzation activity of CrrB, and P151L mutation mediate the resistance of bacteria to the enhancement of 666-15. Our results demonstrated the potential of 666-15 in clinical application and support the further development of a PB synergist based on this compound.